Rivaroxaban versus aspirin for prevention of covert brain infarcts in patients with embolic stroke of undetermined source: NAVIGATE ESUS MRI substudy - Sharma, Mukul; Smith, Eric E; Pearce, Lesly A; Perera, Kanjana S; Kasner, Scott E; Yoon, Byung-Woo; Ameriso, Sebastian F; Puig, Josep; Damgaard, Dorte; Fiebach, Jochen B; Muir, Keith W; Veltkamp, Roland C; et al. (International journal of stroke, 2022)
BACKGROUND: Covert brain infarcts are associated with important neurological morbidity. Their incidence in patients with embolic stroke of undetermined source (ESUS) is unknown. AIMS: To assess the incidence of covert brain infarcts and cerebral microbleeds using MRI in a prospective substudy of the NAVIGATE ESUS randomized trial and to evaluate the effects of antithrombotic therapies. METHODS: At 87 sites in 15 countries, substudy participants were randomly assigned to receive rivaroxaban 15 mg daily or aspirin 100 mg daily and underwent brain MRI near randomization and after study termination. The primary outcome was incident brain infarct (clinical ischemic stroke or covert brain infarct). Brain infarcts and microbleeds were ascertained centrally by readers unaware of treatment. Treatment effects were estimated using logistic regression. RESULTS: Among the 718 substudy participants with interpretable, paired MRIs, the mean age was 67 years and 61% were men with a median of 52 days between the qualifying ischemic stroke and randomization and a median of seven days between randomization and baseline MRI. During the median (IQR) 11 (12) month interval between scans, clinical ischemic strokes occurred in 27 (4%) participants, while 60 (9%) of the remaining participants had an incident covert brain infarct detected by MRI. Assignment to rivaroxaban was not associated with reduction in the incidence of brain infarct (OR 0.77, 95% CI 0.49, 1.2) or of covert brain infarct among those without clinical stroke (OR 0.85, 95% CI 0.50, 1.4). New microbleeds were observed in 7% and did not differ among those assigned rivaroxaban vs. aspirin (HR 0.95, 95% CI 0.52-1.7). CONCLUSIONS: Incident covert brain infarcts occurred in twice as many ESUS patients as a clinical ischemic stroke. Treatment with rivaroxaban compared with aspirin did not significantly reduce the incidence of covert brain infarcts or increase the incidence of microbleeds, but the confidence intervals for treatment effects were wide.Registration: https://www.clinicaltrials.gov. Unique identifier: NCT02313909.
Keywords: Magnetic Resonance Imaging; intrakraniální embolie; Embolic Stroke; magnetická rezonanční tomografie; Humans; Stroke; Intracranial Embolism; Double-Blind Method; Female; Aged; mozkový infarkt; Prospective Studies; senioři; dvojitá slepá metoda; embolická cévní mozková příhoda; lidé; covert stroke; cerebrální krvácení; rivaroxaban; Brain Infarction; cévní mozková příhoda; Anticoagulation; ESUS; ženské pohlaví; randomized clinical trial; Male; Aspirin; Cerebral Hemorrhage; Rivaroxaban; mužské pohlaví; prospektivní studie; cerebral microbleeds; embolic stroke; inhibitory faktoru Xa; Factor Xa Inhibitors